2007
DOI: 10.2147/tcrm.2007.3.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of spontaneous notifications of adverse reactions with aceclofenac, meloxicam, and rofecoxib during the first year after marketing in the United Kingdom

Abstract: Abstract:The objective was to compare the incidence of adverse reactions reported with three nonsteroidal anti-inflammatory drugs with different cyclo-oxygenase (COX)-2 selectivity. All spontaneous adverse reaction notifications in the pharmacovigilance database of the World Health Organisation Collaborating Centre for International Drug Monitoring with aceclofenac, meloxicam, and rofecoxib that were recorded during the first year of marketing were included. The incidence rate (adverse reactions/10 6 defined d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
1
10
0
7
Order By: Relevance
“…Actually, nimesulide was withdrawn from the Spanish and the Finnish markets in 2002 because of an unfavourable benefit-risk balance related to liver injuries [23][24][25]. In the present study, it was found that nimesulide and aceclofenac were associated with the highest risk of liver ADRs, followed by diclofenac and piroxicam, which is in agreement with the literature [6,7,26,27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Actually, nimesulide was withdrawn from the Spanish and the Finnish markets in 2002 because of an unfavourable benefit-risk balance related to liver injuries [23][24][25]. In the present study, it was found that nimesulide and aceclofenac were associated with the highest risk of liver ADRs, followed by diclofenac and piroxicam, which is in agreement with the literature [6,7,26,27].…”
Section: Discussionsupporting
confidence: 91%
“…The last type of serious ADR investigated, thrombotic cardiovascular events, was very rarely reported to the French pharmacovigilance system, as in other systems [26].…”
Section: Discussionmentioning
confidence: 99%
“…The use of non-steroidal anti-inflammatory drugs (NSAIDs) is the most preferred method for pain control in orthodontics but the overuse of analgesics and their potential side effects particularly in children have raised a concern over their use (10). Experimental and clinical studies have shown that NSAIDs can delay or inhibit tooth movement by inhibiting periodontal inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…В Великобритании в течение года изучали побоч-ные эффекты ацеклофенака по сравнению с таковыми ме-локсикама и рофекоксиба [17]. Частота побочных эффек-тов, рассчитанная на 1 млн суточных приемов препарата, составила 8,7 (6,1-12,0) для ацеклофенака и 24,8 (23,1-26,6) и 52,6 (49,9-55,4) для мелоксикама и рофекоксиба соответственно.…”
unclassified
“…Наиболее часто отмечались кожные проявления, затем шли желудоч-но-кишечные, печеночные, почечные осложнения, сравни-тельно редко регистрировались сердечно-сосудистые нару-шения. Самой высокой была частота серьезных побочных эффектов со стороны ЖКТ при использовании кетопрофе-на, пироксикама и напроксена (6,87; 6,54 и 5,07 соответст-венно), со стороны печени при приеме нимесулида и ацек-лофенака (4,53 и 3,67 соответственно), со стороны кожных покровов при применении мелоксикама (3,15), со стороны почек при лечении теноксикамом (3,17). Таким образом, ацеклофенак (аэртал) широко ис-пользуется при неспецифической боли в спине и многих других заболеваниях.…”
unclassified